2014
DOI: 10.1590/0103-6440201302348
|View full text |Cite
|
Sign up to set email alerts
|

Periapical Status and Prevalence of Endodontic Treatment in Institutionalized Elderly

Abstract: The aim of this study was to determine the prevalence and frequency of apical periodontitis and root fillings in 450 institutionalized Brazilian elderly. The teeth with apical periodontitis were assessed using the Periapical Index (PAI) score. A total of 942 teeth were evaluated in 98 subjects (57 females and 41 males) with mean age of 74 years. The observed frequency of total edentulous subjects was high (76%) in this population. A total of 126 teeth showed root fillings, of these only 46 (36.5%) were scored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
2
26
1
2
Order By: Relevance
“…This is in accordance with previous investigations having reported similar results (ranging from 8.8% to 13.4%) [45, 57]. Altogether, 44.9% of the endodontically treated teeth were associated with apical periodontitis, and this again corresponded well with results from other studies [7, 9, 14, 15, 58, 59].…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with previous investigations having reported similar results (ranging from 8.8% to 13.4%) [45, 57]. Altogether, 44.9% of the endodontically treated teeth were associated with apical periodontitis, and this again corresponded well with results from other studies [7, 9, 14, 15, 58, 59].…”
Section: Discussionsupporting
confidence: 93%
“…18 Age-related changes of dental pulp complex influence the frequency of endodontic treatment in elderly people. 30 Besides, younger individuals tend to attend regular check-up more often when compared to elderly and thus they have a lower incidence of caries and periodontal diseases. 31 In various studies, caries has been shown to be more prevalent in women because of such mechanisms: earlier eruption of teeth in girls, hormonal fluctuations in pregnancy, the biochemical composition of saliva, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, data from endodontic epidemiological surveys may contribute to the improvement of this knowledge 7 . Investigations on the prevalence of pulp and periradicular diseases in the Brazilian population produced few studies [8][9][10][11] and most of them were conducted exclusively based on radiographic assessments for the diagnosis of such infections. Considering the importance of epidemiological investigations, the objective of this study was to determine the prevalence of pulp and periradicular diseases diagnosed in a Brazilian subpopulation, correlating this information to gender, age group and most affected teeth.…”
Section: Introductionmentioning
confidence: 99%